2010
DOI: 10.3168/jds.2010-3061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravenous glucose infusion and nutritional balance on serum concentrations of nonesterified fatty acids, glucose, insulin, and progesterone in nonlactating dairy cows

Abstract: The objective of this study was to evaluate serum concentrations of nonesterified fatty acids, glucose, insulin, and progesterone in nonlactating dairy cows according to nutritional balance and glucose infusion. Ten nonlactating, ovariectomized Gir x Holstein cows were stratified by body weight (BW) and body condition score (BCS) on d -28 of the study, and randomly assigned to 1) negative nutrient balance (NB) or 2) positive nutrient balance (PB). From d -28 to d 0, cows were allocated according to nutritional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
3
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 46 publications
1
18
3
4
Order By: Relevance
“…However, the use of this hormone seems to be associated with an increase in the activity of the enzyme GGT, which may explain a marked elevation on GGT activity found on day 15 on all animals from group A, differing from the control group and exceeding the amounts related to the species. Similar results were found by Vieira et al (2010) and Araújo (2014), who verified the increase of this hepatic enzyme after using BST, but they did not give a plausible explanation for this fact. In this case, it is necessary to analyze very carefully this parameter because GGT is an indicator of cell damage and dysfunction of hepatic metabolism.…”
Section: Discussionsupporting
confidence: 91%
“…However, the use of this hormone seems to be associated with an increase in the activity of the enzyme GGT, which may explain a marked elevation on GGT activity found on day 15 on all animals from group A, differing from the control group and exceeding the amounts related to the species. Similar results were found by Vieira et al (2010) and Araújo (2014), who verified the increase of this hepatic enzyme after using BST, but they did not give a plausible explanation for this fact. In this case, it is necessary to analyze very carefully this parameter because GGT is an indicator of cell damage and dysfunction of hepatic metabolism.…”
Section: Discussionsupporting
confidence: 91%
“…Previous results from our laboratory have shown that peripheral concentrations of insulin potentially modulates the hepatic metabolism of P 4 (Moriel et al, 2008;Lopes et al, 2009;Vieira et al, 2010Vieira et al, , 2013. Elevated insulin concentrations reduced hepatic expression of P 4 catabolic enzymes P450 2C and P450 3A (Lemley et al, 2008;Vieira et al, 2013), which may further increase circulating concentrations of P 4 (Moriel et al, 2008;Lopes et al, 2009;Vieira et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated insulin concentrations reduced hepatic expression of P 4 catabolic enzymes P450 2C and P450 3A (Lemley et al, 2008;Vieira et al, 2013), which may further increase circulating concentrations of P 4 (Moriel et al, 2008;Lopes et al, 2009;Vieira et al, 2010). Accordingly, Vieira et al (2013) reported that dairy cows in adequate nutritional status receiving jugular glucose infusion (3 h at a rate of 0.5 g/kg of BW) had greater circulating insulin concentrations and reduced hepatic mRNA expression of P 4 catabolic enzymes CYP2C19 and CYP3A4 compared with cohorts receiving saline infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Alguns estudos sugerem haver uma menor metabolização de P4 em situações de alta insulina sanguínea (COOKE et al, 2012;LEMLEY et al, 2008SMITH et al, 2006;VIEIRA et al, 2010). Como a concentração da insulina pode ser maior após a ingestão de alimento, parece contraditório poder haver um efeito protetor dela sobre a metabolização de hormônios, já que, como mencionado acima, a IMS aumenta o fluxo sanguíneo hepático e favorece a metabolização de hormônios esteroides.…”
Section: )unclassified
“…Diferenças nos padrões de fermentação ruminal ou nos dados relativos à produção leiteira e desempenho de ruminantes recebendo milho e polpa cítrica são descritas em inúmeros estudos (BAMPIDIS; ROBINSON, 2006;BEN-GHEDALIA et al, 1989;BRODERICK;SIMONS, 2002 COOKE et al, 2012;MORIEL et al, 2008;SMITH et al, 2006;VIEIRA et al, 2010). No presente estudo, no entanto, esse efeito "protetor" não foi relacionado à menor expressão gênica das enzimas que metabolizam a P4 (CYP2C19, CYP3A4, AKR1D1, AKR1C4), visto que não foi encontrada diferença na expressão gênica (Tabela 10), diferente do descrito por Lemley et al (2008).…”
Section: Hormônios E Metabólitosunclassified